COMPARATIVE ANALYSIS OF FINANCIAL SYSTEMS OF THE CANADA AND THE USA - DERKACH, Tetiana (Scientific journal «World of Finance», 2020)
Introduction. To determine the strategic goals of transforming the financial system of Ukraine, it is especially important to study the experience of successful and effective world economies. The iconic examples of such systems are the financial systems of Canada and the United States. The purpose of this article is to analyze the dynamics of the United States and Canadian financial systems’ indicators and determine the characteristics of the development of these countries in terms of their future closest financial integration. Methods. The research methodology was based on a combination of such scientific methods as: generalization, graphic and comparative analysis, analysis and synthesis, this made possible to determine the development details of the USA and Canadian financial system and the possibilities for their financial sector further integration and harmonization. Results. The USA and Canadian financial systems are analyzed, especially, the causes and consequences of the financial integration of these systems, as well as possible ways for their further development are thoroughly studied. Such stability indicators of the financial system as inflation, money supply, interest rate dynamics and public debt are researched. Risk assessment of the further development of the financial system of the USA and Canada is also done. Conclusions. The Canadian and US financial systems are closely interconnected through many years of cooperation. Accordingly, the risks in these systems are the same, and factors that are similar for both countries hinder their development. Although, regardless of these factors, in general, the development of the financial systems of the United States and Canada is stable and consistent.